-7p+6p=-3

Simple and best practice solution for -7p+6p=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7p+6p=-3 equation:


Simplifying
-7p + 6p = -3

Combine like terms: -7p + 6p = -1p
-1p = -3

Solving
-1p = -3

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '-1'.
p = 3

Simplifying
p = 3

See similar equations:

| 695/x=139 | | 70+x=42+3x | | (5x^2-25)(2x^2-36)=0 | | 4xy=76 | | 9(x+3)+4=9x+9 | | (37x-15)+(44x-29)=360 | | (3y^1/4)^3 | | (37x-15)+(44x-29)=180 | | -7+15=-16 | | (3/4x-2/3)=(1/6) | | 3x^2+9x+4x+12= | | 2g+4(-8+3g)=1-g | | 3y-2(y-1)/6=-2 | | -1/5r=24/5 | | 12(x+8)=4(24+3n) | | xb=-7 | | -9=11m-3.4 | | 88x-55=y | | 0.8x-10=2.3x-25 | | 4(x-30)=5-3x | | a-b=x | | 12x/35-x/7=1 | | 55=4x+y | | 3x+21=46-2x | | 2t^2=30t | | 0.005(x+3)=0.006x+0.013 | | 378g*6=47g | | -2x-5x=9x-12 | | 26x+8=5(5x+6) | | 4/9//-5/6 | | 2b/3a÷4b/9a^4b^5 | | 2a-3a=a |

Equations solver categories